Sediment core description of gravity core GeoB19289-1 (GC37) recovered during R/V Meteor expedition M112 at Sartori MV in the Calabrian Arc, Mediterranean Sea - Mechthild Doll; Gerhard Bohrmann (PANGAEA, 2024)
Sediment core GeoB19289-1 (GC37) was collected during R/V Meteor expedition M112 using a gravity corer. The position is close to the Sartori Mud Volcano located in the Calabrian accretionary prism (Mediterranean Sea). The gravity core was longitudinally split directly after recovery on board of cruise M112. The archive halve was photographed using the smartCIS1600 line scan technique of the MARUM GeoB Core repository at a 500-dpi resolution in 2019. To investigate lithological changes in more detail, a macroscopic core description is prepared. The core description provides information regarding core length, exact position, water depth, number of core sections, core image, color, lithology, sedimentary structures and a descriptive text. Sediment color was determined qualitatively using Munsell soil color charts.